Pharmacogenomics, biomarker network, and allele frequencies in colorectal cancer - López-Cortés, Andrés; Paz-y-Miño, César; Guerrero, Santiago; Jaramillo-Koupermann, Gabriela; León Cáceres, Ángela; Intriago-Baldeón, Dámaris P.; García-Cárdenas, Jennyfer M.; Guevara-Ramírez, Patricia; Armendáriz-Castillo, Isaac; Leone, Paola E.; Quiñones, Luis Abel; Cayún, Juan Pablo; et al. (The pharmacogenomics journal, 2020)
Colorectal cancer is one of the leading causes of cancer death worldwide. Over the last decades, several studies have shown that tumor-related genomic alterations predict tumor prognosis, drug response, and toxicity. These observations have led to the development of several therapies based on individual genomic profiles. As part of these approaches, pharmacogenomics analyses genomic alterations which may predict an efficient therapeutic response. Studying these mutations as biomarkers for predicting drug response is of a great interest to improve precision medicine. We conduct a comprehensive review of the main pharmacogenomics biomarkers and genomic alterations affecting enzyme activity, transporter capacity, channels, and receptors; and therefore the new advances in CRC precision medicine to select the best therapeutic strategy in populations worldwide, with a focus on Latin America.